2009
DOI: 10.1007/s11548-009-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving education on C-arm operation and radiation protection with a computer-based training and simulation system

Abstract: The virtX-approach of simulating radiograph generation including patient positioning and scattered radiation was evaluated positively concerning its suitability for imparting knowledge regarding radiation protection and C-arm operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Th ere is a large body of research that is yet to be applied to simulated learning. Eleven studies were identifi ed that reported on simulation techniques specifi c to DR (n = 7) [13][14][15][16][17][18][19] and RT (n = 4). [20][21][22][23] One study, assessing the learning eff ectiveness of a live simulated scenario 14 of a critical incident within the computed tomography suite demonstrated improved student performance when they were given the opportunity to view and critique a staged simulated scenario before becoming immersed in that scenario themselves.…”
Section: Image Library Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Th ere is a large body of research that is yet to be applied to simulated learning. Eleven studies were identifi ed that reported on simulation techniques specifi c to DR (n = 7) [13][14][15][16][17][18][19] and RT (n = 4). [20][21][22][23] One study, assessing the learning eff ectiveness of a live simulated scenario 14 of a critical incident within the computed tomography suite demonstrated improved student performance when they were given the opportunity to view and critique a staged simulated scenario before becoming immersed in that scenario themselves.…”
Section: Image Library Nmentioning
confidence: 99%
“…Th ese results support a carefully staged simulated learning in a graded framework. Other identifi ed DR simulated learning activities included online interactive tutorial systems 15-18 a virtual reality soft ware program 19 and a simulated magnetic resonance scanner 13 but none were evaluated for their learning eff ectiveness.…”
Section: Image Library Nmentioning
confidence: 99%
“…Optimizing the position of any C-arm device (to minimize radiation exposure) is challenging since the context, the imaging parameters, and the patient's and staff's positioning need to be considered in the MC simulations. As in Bott et al (22), the real C-arm imaging parameters (tube kilovoltage, filtration, aperture angle and beam projection), together with the X-ray photon scattering process, are all considered by the simulation. These can be extracted from the C-arm device application programming interface (API).…”
Section: Interventional 3d Augmented Reality In Orthopedic Trauma Anmentioning
confidence: 99%
“…To improve training in C-arm operation, the virtX (virtual x-ray) computer-based training system was developed by an interdisciplinary team of medical informatics specialists, trauma surgeons, and radiologists (13)(14)(15)(16)). The virtX system was designed to fill the gap between the teaching of theoretical principles of C-arm operation and the actual use of a C-arm with two additional stages of interactive training: (a) training in the so-called virtual mode (training mode 1), consisting of a series of computer-based imaging exercises in which C-arm use in various surgical procedures is simulated by the trainee on a desktop personal computer (PC) with a keyboard, mouse, and monitor; and (b) training in a simulated operating room environment, in the so-called real mode (training mode 2), which involves manipulation of an actual C-arm (without any actual imaging or radiation), operating table, and mannequin while the computer-based simulation system provides cues and performance feedback (Fig 1).…”
Section: Virtx System Design Functionality and Operationmentioning
confidence: 99%